Doing exposed correction in the language class-room: A conversation analysis perspective - Tůma, František; Fořtová, Nicola (Yearbook of the Poznan Linguistic Meeting, 2020)
Exposed correction can be seen as a tool whose use on the one hand temporarily stops the progressivity of the talk, but at the same time makes it possible for the speakers in interaction to clarify problems that have occurred, both in mundane conversation and institutional talk. Using conversation analysis, a dataset of 18 teaching hours (1585 minutes of video-recordings of whole-class work in total) was examined to identify and describe the practices used by learners and teachers in English as a foreign language (EFL) classrooms when conducting exposed correction. The analysis shows that in exposed correction sequences there seems to be a requirement for the learners to produce a reaction to teacher correction. While learners typically repeat the correct form after the teacher has corrected them in a correction sequence that the learners initiated by displaying trouble producing the target language form, teacher-initiated sequences tend to generate minimal post-expansion on the part of the learners. When no student response comes, the teacher may expand the correction sequence.